Mechanical properties of polypropylene composites reinforced by hydrolyzed and microfibrillated Kevlar fibers. (28th July 2018) - Fu, Sirui; Yu, Bowen; Tang, Wei; Fan, Mao; Chen, Feng; Fu, Qiang
Abstract: As a traditional general plastic, polypropylene (PP) has been widely used in daily life. Glass fibers are often used to further reinforce the properties of PP for its application in engineering area. However, there are still some drawbacks existing for glass fibers filled polypropylene composites, such as high filler content, easy fracture of glass fibers and damage to the machines during processing. Therefore, organic fibers are considered as an ideal candidate to replace glass fibers. In this work, short Kevlar fibers (KFs) modified by ball milling in phosphoric acid and surface hydrolyzation were introduced to PP matrix to improve the interfacial interaction and mechanical properties. It is found that KFs were exfoliated into several flaky microfibers and then broken into pieces during the ball milling process. With the aid of phosphoric acid, the KFs can be split further thereby increasing specific surface area greatly. Then the original and milled KFs were hydrolyzed by NaOH aqueous solution in order to introduce OH group on the surface of KFs. The dispersion and mechanical properties of PP reinforced with various KFs, including original, ball milled, and hydrolyzed, were investigated and compared. It was found that the combination of ball milling in phosphoric acid and surface hydrolyzation is the most effective way for enhancement of interfacial reaction and mechanical properties. Adding 10 wt. % of KFs could lead to an increase of tensile strength of PP from 30 MPa to 47 MPa, which only can be achieved by adding at least of 25 wt. % of glass fibers. The tensile test shows that hydrolyze of KFs surface are a more important factor to promote the interfacial interaction between fibers and matrix. Our work demonstrates that PP can be enhanced efficiently by the introduction of hydrolyzed and microfibrillated KFs. Although KFs are expensive compared with glass fiber at this moment, their high reinforcement efficiency and toughness could make them competitive as reinforcing filler for the preparation of advanced polymer composites with excellent mechanical and processing properties.